ANTECENDENTS OF CONSUMERS PERCEPTION AND ITS INFLUENCE TOWARDS PURCHASE INTENTION ON COSMETICS PRODUCT - Pramono Hari Adi (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2015)
The aim of this research is to analyze the effects of celebrity endorsement on consumer perception and purchase intention of cosmetic product. The populations in this study were cosmetic users in Purwokerto region. By employing cluster sampling, 120 females who have ever watched cosmetic advertisement were chosen as the sample. The variables of this research were analyzed by using Structural Equation Modeling (SEM). From the analysis results, it was revealed that Trustworthiness had no effect on consumer perception whilePhysical attractiveness and Expertise had positive effect on consumer perception and also consumer perception had positive effect on purchase intention. Those results imply that the company should choose a celebrity endorser who are possesing several aspects such as honesty, trustworthiness, and sincerity in advertising. Beside that, the company should give priority on physical attractiveness of celebrity endorser. Moreover, the company should create promotion through advertising with a celebrity endorser who has various expertises such as knowledgeabout the productsand experience to become a star of cosmetics product